2009
DOI: 10.2337/db09-0658
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Novel Single-Chain Antibodies by Phage-Display Technology to Direct Imaging Agents Highly Selective to Pancreatic β- or α-Cells In Vivo

Abstract: OBJECTIVENoninvasive determination of pancreatic β-cell mass in vivo has been hampered by the lack of suitable β-cell–specific imaging agents. This report outlines an approach for the development of novel ligands homing selectively to islet cells in vivo.RESEARCH DESIGN AND METHODSTo generate agents specifically binding to pancreatic islets, a phage library was screened for single-chain antibodies (SCAs) on rat islets using two different approaches. 1) The library was injected into rats in vivo, and islets wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 32 publications
2
49
0
2
Order By: Relevance
“…Next, soluble SCA B5 was radioactively labelled and its binding properties were tested in INS-1, beta TC6 and AR42J cells in vitro. These characteristics were then compared with those of the beta cell-specific SCAs identified previously [18]. Of note, in contrast to the BRASIL method, this assay was performed at 37°C (except studies for binding affinity and binding sites).…”
Section: Generation Of Beta Cell-targeting Scasmentioning
confidence: 99%
See 3 more Smart Citations
“…Next, soluble SCA B5 was radioactively labelled and its binding properties were tested in INS-1, beta TC6 and AR42J cells in vitro. These characteristics were then compared with those of the beta cell-specific SCAs identified previously [18]. Of note, in contrast to the BRASIL method, this assay was performed at 37°C (except studies for binding affinity and binding sites).…”
Section: Generation Of Beta Cell-targeting Scasmentioning
confidence: 99%
“…Phage-display technology may be a suitable way to overcome these limitations [15][16][17]. By applying this approach to rats in vivo or freshly isolated rat islets in vitro, we have recently reported the isolation of single-chain antibodies (SCAs) highly specific for either pancreatic beta or alpha cells [18]. However, these approaches applied collagenase-digestion for islet isolation, which might alter substantially the surface profile of the islet cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A monoclonal antibody with these characteristics (recognising an uncharacterised antigen, IC2) was generated in 1986 and was subsequently used to probe beta cells in vivo, although the analyses of specificity and correlation with beta cell mass were performed in isolated pancreases [11,12]. The fact that this antibody is a large IgM class antibody and has a long plasma half-life is likely to reduce its application in human beta cell imaging owing to a poor signal-to-noise ratio [7] Promising probes were recently generated by panning a phage display in vivo and in vitro [13]. A single-chain antibody was identified that efficiently labels beta cells in vivo, and radiolabelling demonstrated a good correlation with beta cell mass in the isolated organ.…”
mentioning
confidence: 99%